2017
DOI: 10.24297/ijct.v16i2.5931
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Facebook on Academic Performance for Undergraduate Students at Charmo University

Abstract: Facebook occupies an important part of people's time and life due to the recent developments in the field of communication technologies (CT). This paper aims at investigating the Facebook impact (FI) on undergraduate students at Charmo University. Moreover, Facebook also has a great impact on students' life studies at universities. However, in addition to its benefits, Facebook also has some side effects on students' life study. In regard to data collection, an online survey was used in which 15 questions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The study found that Facebook addiction has negative relationship with academic performance of the students, as indicated by the last semester’s GPA report [β: -10.01, 95% CI: -10.85,-(-9.18)]. This finding is in agreement with the previous studies conducted in India [ 11 ], Iraq [ 9 ], Pakistan [ 35 ], and Sri Lanka [ 10 ]. Although various studies have found that Facebook addiction has negative effects on university students, a study from Pakistan [ 4 ] found that Facebook could help with communication and information gathering.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The study found that Facebook addiction has negative relationship with academic performance of the students, as indicated by the last semester’s GPA report [β: -10.01, 95% CI: -10.85,-(-9.18)]. This finding is in agreement with the previous studies conducted in India [ 11 ], Iraq [ 9 ], Pakistan [ 35 ], and Sri Lanka [ 10 ]. Although various studies have found that Facebook addiction has negative effects on university students, a study from Pakistan [ 4 ] found that Facebook could help with communication and information gathering.…”
Section: Discussionsupporting
confidence: 89%
“…As the studies revealed, extended use of Facebook has led to poor academic performance, bullying activities, decreased face-to-face contact, sleep disruptions, and mental health disturbances [ 8 , 9 ]. Log-in-related distractions such as uploading, commenting, and chatting with friends are leading to procrastination of learning activities [ 8 ] and sinking academic success among university students currently [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation